Three decades of sea water abstraction by Kapar power plant (Malaysia): What impacts on tropical zooplankton community? - Chew, L.L.; Chong, V.C.; Wong, R.C.S.; Lehette, P.; Ng, C.C.; Loh, K.H. (2015)
Zooplanlcton samples collected before (1985-86) and after (2013-14) the establishment of Kapar power station (KPS) were examined to test the hypothesis that increased sea surface temperature (SST) and other water quality changes have altered the zooplankton community structure. Elevated SST and reduced pH were detected between before and after impact pairs, with the greatest impact at the station closest to KPS. Present PAHs and heavy metal concentrations are unlikely causal factors. Water parameter changes did not affect diversity but community structure of the zooplankton. Tolerant small crustaceans, salps and larvaceans likely benefited from elevated temperature, reduced pH and shift to a more significant microbial loop exacerbated by eutrophication, while large crustaceans were more vulnerable to such changes. It is predicted that any further rise in SST will remove more large-bodied crustacean zooplankton, the preferred food for fish larvae and other meroplankton, with grave consequences to fishery production. (C) 2015 Elsevier Ltd. All rights reserved.